Sensitivity of non-small cell lung cancer to erlotinib is regulated by the Notch/miR-223/FBXW7 pathway. Issue 3 (21st June 2017) - Zhang, Haiwei; Chen, Fanglin; He, Yongpeng; Yi, Lin; Ge, Chuang; Shi, Xiaolong; Tang, Chao; Wang, Donglin; Wu, Yongzhong; Nian, Weiqi
Abstract : Recent evidence supports a role for microRNA-223 (miR-223) in modulating tumor cell sensitivity to chemotherapeutic drugs; however, its role in cellular resistance to the effects of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) used in treatment of non-small cell lung cancer (NSCLC) remains to be elucidated. The levels of miR-223 in parental cell line (HCC827) and erlotinib resistant HCC827 cell line (HCC827/ER) were detected by qRT-PCR. HCC827/ER cells were treated with MK-2206 to block the Akt signaling pathway or RO4929097 to block the Notch signaling pathway, and then transfected with an miR-223 inhibitor or interference expression plasmid of F-Box/WD repeat-containing protein 7 (FBXW7) or insulin-like growth factor 1 receptor (IGF1R). HCC827 cells were transfected with miR-223 mimics. Next, CCK-8, colony formation, and flow cytometric apoptosis assays were used to assess cell resistance to erlotinib. When compared with its expression in HCC827 cells, miR-223 expression was significantly up-regulated in HCC827/ER cells. Blocking either the Akt or Notch signaling pathway and reducing miR-223 expression resulted in decreased resistance in HCC827/ER cells. Conversely, increasing miR-223 expression induced cell resistance to erlotinib in HCC827 cells. miR-223 enhanced resistance to erlotinib by down-regulating FBXW7 expression. Reducing FBXW7 expression lowered resistance to erlotinib in HCC827/ER cells, while interference with expression of IGF1R produced no significant effect. This study demonstrated that NSCLC cells can up-regulate their levels of miR-223 expression via the Akt and Notch signaling pathways. miR-223 may serve as an important regulator of erlotinib sensitivity in NSCLC cells by targeting FBXW7 .